Generative AI and the Future of the Humanities - J. Gavin, Dana. author. (orcid)0000-0003-2605-7542 Link aut Link
VIII, 116 p. 1 illus.
Keywords: This book offers scholars in the humanities a way to think critically about generative AI and the impact of technocaptialism on foundational, and essentially human, crafts such as reading and writing. The target audience includes educators and scholars in higher education and K-12, as well as anyone interested in how critical thinking and writing will be taught in the future. For those who only know the term "ChatGPT," this book is a resource for understanding how pervasive and ubiquitous generative AI already is in our lives; for those familiar with OpenAI and other developers, this book provides greater context for the effects of such technology on our creative functionality. Dana J. Gavin, PhD, is the Director of the Writing Center at Dutchess Community College, USA. She recently earned her PhD in English (with concentrations in Literature & Culture and Technology & New Media) from Old Dominion University. Her research into serialized crime fiction produced through the nineteenth-century British publishing industry teed her up for the November 2022 crash-landing of ChatGPT into our educational worlds. Teaching writing and facilitating learning experiences where people can become confident communicators are her primary objectives.